2019
DOI: 10.1016/j.cities.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Greening the post crisis. Collectivity in private and public community gardens in València (Spain)

Abstract: Unlike other Western European countries, community gardens have appeared very recently in Spain, and they have rapidly increased during the last decade. Community gardens have adopted different forms -rental, municipal and associative-with contrasted managerial practices. This paper analyzes collectivity of community gardens in València (Spain), including private initiatives, through semi-structured interviews conducted in different gardens of the València Metropolitan Area. Results show how the financial cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 59 publications
0
6
0
2
Order By: Relevance
“…Another potential insight for policy and programs stems from the demonstrated roles of immigrant farm workers in specific forms of agri-food alternatives (detailed in Results and defined in the Introduction) that have continued to expand in Spain [39]. Participation in these programs, as described above, can potentially strengthen the resilience and social inclusion of immigrants in Spain and elsewhere (e.g., [60,91,92]).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential insight for policy and programs stems from the demonstrated roles of immigrant farm workers in specific forms of agri-food alternatives (detailed in Results and defined in the Introduction) that have continued to expand in Spain [39]. Participation in these programs, as described above, can potentially strengthen the resilience and social inclusion of immigrants in Spain and elsewhere (e.g., [60,91,92]).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of NCUA yielded in four categories of social benefits from gardening: mental health and wellbeing, society economic growth and employment opportunities, nutrition, and social cohesion: First, mental health and wellbeing, where it was found that living in green environments was associated with reduced instances of depression and helped reduce personal feelings of anxiety [60], with an 8-12% reduction in mortality risk [9,35,61]. Secondly, the society economic growth and employment opportunities, where a number of professionals, technicians, and farmers are hired to manage the UAP by offering help and advice to users [62], making these NCUA areas a "refuge sector" for unemployed workers, retired people, or failed entrepreneurs [46,52]. In the third place comes the nutrition aspect, where gardens expand access to healthy nutritional fruits and vegetables in economically significant quantities, and where fruit and vegetable consump-tion has improved [53,63], increasing food security and providing livelihoods for urban dwellers [64].…”
Section: Social Benefitsmentioning
confidence: 99%
“…Economic benefits: the implementation of NCUA practices helps to promote community resilience and stimulate economic development [42]. The analysis of this aspect identified two sub-categories, namely cost reduction and income generation: cost reduction is related to people saving money on their groceries [43], by reducing the prices and making them accessible to low-income households [44]; income generation relates specifically to the fact that these gardens offer the opportunity to develop an agricultural system that matches their values and is adapted to their needs, and which can be translated into revenue [45,46].…”
mentioning
confidence: 99%
“…La superficie artificial de Valencia aumentó en 8000 ha durante el período 1984-2011 (Fernández y López, 2015). La expansión urbana también fue acelerada por el boom inmobiliario español de 1998-2008, cuyas consecuencias activaron nuevos movimientos sociales para proteger la vida en la huerta de Valencia (Palau-Salvador et al, 2019). En 2000, una iniciativa legislativa popular recogió 118 000 firmas a favor de una ley y un plan territorial específico para proteger la huerta valenciana.…”
Section: Introductionunclassified
“…Así, a lo largo de todos estos años hasta la aprobación en 2018 del PAT HUERTA (Plan de Acción Territorial de la Huerta de Valencia), han surgido iniciativas disruptivas para proteger este entorno hortelano. Sin duda, hoy la ciudad presenta un liderazgo más equilibrado entre las instituciones públicas, la sociedad civil, las iniciativas del sector privado y el resto de grupos y actores territoriales interesados en la huerta de Valencia (Palau-Salvador et al, 2019).…”
Section: Introductionunclassified